"Estudio de efecto de los aceites de sacha inchi (Plukenetia huayllabana), ajonjolí (Sessamun indicum), maní (Arachis hypogaea), en la conservación de paiche (Arapaima gigas)" - Plua Montiel, Jhoan Alfredo (2020)
The aim of this project is to study the effect of sacha inchi (Plukenetia huayllabambana), sesame (Sesamum indicum) and peanut (Arachis hypogaea) oilseeds, extracted by two pressing methods (warm and cold). These are applied on the conservation of paiche (Arapaima gigas ) using two different cuts (loin and belly) in two different containers (glass and can). Consequently, we proceeded to study the properties of both; the fatty acid profile and the bromatological properties of each of the oils, types of cuts and preserved fish, carrying out a material balance in order to determine the performance of the oils, as well as preserves’, determining the best treatments through a sensory evaluation. First, the development of the research was carried out by obtaining the different oilseeds, and then the oil was extracted to proceed with the preparation of these preserves. To determine the difference between the properties of both, the fatty acid profile and bromatological properties, two designs were used, using an AxB factorial design for oil extraction with 3 repetitions (Factor A: Types of oilseeds, Factor B: Extraction methods). In addition, for the elaboration of the preserves, a factorial design was carried out AxBxC with 3 repetitions, (Factor A: Oil obtained, Factor B: types of cuts and Factor C: Types of containers). To establish the effects between the treatment levels, Tukey's significance test was applied (p <0.05), the result of the data obtained was analyzed by the statistical package "STATGRAPHICS" and "STATISTICA". Regarding the extraction, sacha inchi and sesame oilseeds were observed, both, warm and cold pressing, they had the best characteristics in polyunsaturated fatty acids as well as in relative density, pH and humidity, while for acidity and peroxide index peanut oilseeds had better results applying the two extraction methods. On the other hand, preserved paiche had better results where sacha inchi or sesame oilseeds were applied, using the type of loin cut, influenced by the glass container. Keywords: Oilseeds, oil, extraction, conservation, paiche.